Indigenous African enterprise : the Igbo traditional business school (I-TBS) - Adeola, Ogechi (Emerald Publishing Limited, 2020)
This volume of Advanced Series in Management traces the origins, development, and key themes of the business practices of Nigeria's south-eastern Igbos including apprenticeships, entrepreneurial clusters, sales practices, conflict management, talent recruitment, indigenous financial practices, locally-generated venture capital, family businesses, and succession planning. The Igbo Traditional Business School (I-TBS) is not a conventional academic institution as it operates outside the classroom. Though without a library, or even an address, its tradition of lifelong entrepreneurial learning is an important area to explore. At a time when there is increased interest in Africa-centric business models, it is valuable to consider sustainable business prototypes built on established cultural practices, norms, and values. Academics will find the examination of innovative I-TBS business practices, a valuable contribution to sustainable development discourse in Africa and frontier markets. Practitioners and policymakers will gain insights into the unique practices of an indigenous entrepreneurship system in an African context, with implications for socioeconomic advancements.
Keywords: Igbo (African people) -- Economic conditions.; Business enterprises -- Nigeria.; Entrepreneurship -- Nigeria.; Ibo (Peuple d'Afrique) -- Conditions économiques.; Entreprises -- Nigeria.; Entrepreneuriat -- Nigeria.; Nigeria.; History, Africa, West.; Business enterprises; Entrepreneurship; Igbo (African people) -- Economic conditions; Nigeria